The generation of metabolic changes for the production of high-purity zeaxanthin mediated by CRISPR-Cas9 in Chlamydomonas reinhardtii - Song, Inhwa (Microb Cell Fact, 2020)
BACKGROUND: Zeaxanthin, a major xanthophyll pigment, has a significant role as a retinal pigment and antioxidant. Because zeaxanthin helps to prevent age-related macular degeneration, its commercial use in personalized nutritional and pharmaceutical applications has expanded. To meet the quantitative requirements for personalized treatment and pharmaceutical applications, it is necessary to produce highly purified zeaxanthin. RESULTS: In this study, to meet the quantitative requirements for industrial applications, we generated a double knockout mutant which is gene-edited by the CRISPR-Cas9 ribonucleoprotein-mediated knock-in system. The lycopene epsilon cyclase (LCYE) was edited to the elimination of α-branch of xanthophyll biosynthesis in a knockout mutant of the zeaxanthin epoxidase gene (ZEP). The double knockout mutant (dzl) had a 60% higher zeaxanthin yield (5.24 mg L(− 1)) and content (7.28 mg g(− 1)) than that of the parental line after 3 days of cultivation. Furthermore, medium optimization improved the 3-day yield of zeaxanthin from the dzl mutant to 6.84 mg L(− 1). CONCLUSIONS: A Chlamydomonas strain with the elimination of lutein production by gene editing using CRISPR-Cas9 has been successfully developed. This research presents a solution to overcome the difficulties of the downstream-process for the production of high-purity zeaxanthin.